2020
DOI: 10.1111/all.14140
|View full text |Cite
|
Sign up to set email alerts
|

Profilin is a marker of severity in allergic respiratory diseases

Abstract: Background The capacity of profilin to induce allergic symptoms in patients with respiratory allergy has been questioned. In this sense, the aim of this study was to investigate the correlation between profilin exposure and induction of symptoms in a prospective case‐control study. Methods The concentration of profilin as well as pollen levels in the air was measured. A diary score of symptoms was collected from allergic patients. Seventy‐nine individuals were included in the study; fifty cases and 28 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This is congruent to other recent studies eg from Ruiz-Hornillos et al who found in a prospective case-control study that sensitization to profilin seems to be a marker of severity in patients with rhinoconjunctivitis and asthma mediated by pollen. 20 Previous observations also have suggested the importance of profilin as a marker of evolution and early marker of asthma severity which is in accordance to our results with a higher rate of self-reported asthma among patients sensitized to profilin. 16 , 21 , 22 …”
Section: Discussionsupporting
confidence: 93%
“…This is congruent to other recent studies eg from Ruiz-Hornillos et al who found in a prospective case-control study that sensitization to profilin seems to be a marker of severity in patients with rhinoconjunctivitis and asthma mediated by pollen. 20 Previous observations also have suggested the importance of profilin as a marker of evolution and early marker of asthma severity which is in accordance to our results with a higher rate of self-reported asthma among patients sensitized to profilin. 16 , 21 , 22 …”
Section: Discussionsupporting
confidence: 93%
“…Profilins [20] and polcalcins are important respiratory panallergens. Despite their ubiquity in the plant kingdom, both panallergens are not recognized as major allergens and their clinical relevance remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…1398 Further, recent studies showed that in certain geographic areas profilin sensitization represents a marker of more severe respiratory allergy in patients with pollen-mediated rhino-conjunctivitis and asthma, probably because in most cases it occurs in patients with multiple primary sensitizations to different sources. 1399 B) As a plant food allergen (Table 71)…”
Section: -Clinical Relevance Of Profilinmentioning
confidence: 99%